2023
DOI: 10.3390/ijms241210101
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Zirconia Surface Modification for Dental Implants by Atomic Layer Deposition

Abstract: Zirconia is a promising material for dental implants; however, an appropriate surface modification procedure has not yet been identified. Atomic layer deposition (ALD) is a nanotechnology that deposits thin films of metal oxides or metals on materials. The aim of this study was to deposit thin films of titanium dioxide (TiO2), aluminum oxide (Al2O3), silicon dioxide (SiO2), and zinc oxide (ZnO) on zirconia disks (ZR-Ti, ZR-Al, ZR-Si, and ZR-Zn, respectively) using ALD and evaluate the cell proliferation abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“… 12 Accordingly, various methods of coating zirconia particles on the surface of titanium implants have been studied, but appropriate standards have not yet been established. 15 Zirconia undergoes a phase transition into a monoclinic or tetragonal structure depending on temperature or stress, and this changes its strength or volume. 27 If zirconia is deposited by physical or chemical treatments at high temperatures and pressures using the conventional methods, its films may contain impurities or undergo unexpected phase transitions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 12 Accordingly, various methods of coating zirconia particles on the surface of titanium implants have been studied, but appropriate standards have not yet been established. 15 Zirconia undergoes a phase transition into a monoclinic or tetragonal structure depending on temperature or stress, and this changes its strength or volume. 27 If zirconia is deposited by physical or chemical treatments at high temperatures and pressures using the conventional methods, its films may contain impurities or undergo unexpected phase transitions.…”
Section: Discussionmentioning
confidence: 99%
“… 14 It has been found that zirconia-coated implants have more reliable osseointegration than titanium implants, thereby being composed of histologically mature bone. 14 However, Hayashi et al 15 reported that while many studies have suggested various surface modification procedures of zirconia, appropriate standards have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations